Mechanisms of impaired mitochondrial homeostasis and NAD+ metabolism in a model of mitochondrial heart disease exhibiting redox active iron accumulation - Shannon Chiang (Redox Biology, 2021)
Due to the high redox activity of the mitochondrion, this organelle can suffer oxidative stress. To manage energy demands while minimizing redox stress, mitochondrial homeostasis is maintained by the dynamic processes of mitochondrial biogenesis, mitochondrial network dynamics (fusion/fission), and mitochondrial clearance by mitophagy. Friedreich's ataxia (FA) is a mitochondrial disease resulting in a fatal hypertrophic cardiomyopathy due to the deficiency of the mitochondrial protein, frataxin. Our previous studies identified defective mitochondrial iron metabolism and oxidative stress potentiating cardiac pathology in FA. However, how these factors alter mitochondrial homeostasis remains uncharacterized in FA cardiomyopathy. This investigation examined the muscle creatine kinase conditional frataxin knockout mouse, which closely mimics FA cardiomyopathy, to dissect the mechanisms of dysfunctional mitochondrial homeostasis. Dysfunction of key mitochondrial homeostatic mechanisms were elucidated in the knockout hearts relative to wild-type littermates, namely: (1) mitochondrial proliferation with condensed cristae; (2) impaired NAD+ metabolism due to perturbations in Sirt1 activity and NAD+ salvage; (3) increased mitochondrial biogenesis, fusion and fission; and (4) mitochondrial accumulation of Pink1/Parkin with increased autophagic/mitophagic flux. Immunohistochemistry of FA patients' heart confirmed significantly enhanced expression of markers of mitochondrial biogenesis, fusion/fission and autophagy. These novel findings demonstrate cardiac frataxin-deficiency results in significant changes to metabolic mechanisms critical for mitochondrial homeostasis. This mechanistic dissection provides critical insight, offering the potential for maintaining mitochondrial homeostasis in FA and potentially other cardio-degenerative diseases by implementing innovative treatments targeting mitochondrial homeostasis and NAD+ metabolism.